A period of structural plasticity at the axon initial segment in developing visual cortex - Gutzmann, Annika; Erguel, Nursah; Grossmann, Rebecca; Schultz, Christian; Wahle, Petra; Engelhardt, Maren (Frontiers in Neuroanatomy, 2014)
Cortical networks are shaped by sensory experience and are most susceptible to modifications during critical periods characterized by enhanced plasticity at the structural and functional level. A system particularly well-studied in this context is the mammalian visual system. Plasticity has been documented for the somatodendritic compartment of neurons in detail. A neuronal microdomain not yet studied in this context is the axon initial segment (AIS) located at the proximal axon segment. It is a specific electrogenic axonal domain and the site of action potential (AP) generation. Recent studies showed that structure and function of the AIS can be dynamically regulated. Here we hypothesize that the AIS shows a dynamic regulation during maturation of the visual cortex. We therefore analyzed AIS length development from embryonic day (E) 12.5 to adulthood in mice. A tri-phasic time course of AIS length remodeling during development was observed. AIS first appeared at E14.5 and increased in length throughout the postnatal period to a peak between postnatal day (P) 10 to P15 (eyes open P13–14). Then, AIS length was reduced significantly around the beginning of the critical period for ocular dominance plasticity (CP, P21). Shortest AIS were observed at the peak of the CP (P28), followed by a moderate elongation toward the end of the CP (P35). To test if the dynamic maturation of the AIS is influenced by eye opening (onset of activity), animals were deprived of visual input before and during the CP. Deprivation for 1 week prior to eye opening did not affect AIS length development. However, deprivation from P0 to 28 and P14 to 28 resulted in AIS length distribution similar to the peak at P15. In other words, deprivation from birth prevents the transient shortening of the AIS and maintains an immature AIS length. These results are the first to suggest a dynamic maturation of the AIS in cortical neurons and point to novel mechanisms in the development of neuronal excitability.